Artificial Intelligence and Mental Health Issues: A Narrative Review - Zandra Bonnine V. Salcedo; I Dewa Ayu Eka Purba Dharma Tari; Chadchom Ratsameemonthon; Ratna Yunita Setiyani (Journal of Public Health Sciences, 2023)
The objective of this study is to explore the potential of Artificial Intelligence (AI) in the field of mental health and its impact on the current healthcare system. The focus is to examine the benefits and challenges of using AI in mental health, including the ethics and privacy concerns. The method used in this study is a narrative review approach, which provides an overview of the current state and future possibilities of AI in mental health. The study is based on a comprehensive review of existing literature in the field, including peer-reviewed articles, books, and online resources. AI has the potential to revolutionize the mental health field. With the use of machine learning algorithms, AI can aid in the diagnosis and classification of mental health disorders, provide online platforms for mental health support, improve patient flow in inpatient units, relieve symptoms of depression and anxiety, and transform the future of psychiatry. Despite the potential benefits, there are also critical issues surrounding the use of AI in mental health, including data privacy, accuracy, and ethics. It is crucial for further research to address these challenges and ensure that the development and implementation of AI in mental health upholds ethical standards and prioritizes patient well-being.